Importance of CT imaging in pediatric cochlear implantation: Emphasis the significance of the BCNC width. - Dokoska, M; Nikolovski, N; Nikolova, S; Kopacheva Barsova, G (My University, 2022)
Introduction: Cochlear Implantation (CI), in the past more than 30 years, has become a standard of care for children with profound sensorineural hearing loss. As it became a routine intervention, requests for pre-op images have increased in the work-up for candidates. The optimal protocol for radio-diagnostics has not yet been defined. CT and MRI are complementary methods and both being used for this purpose. An absent cochlear nerve (CN) is the only absolute contraindication to cochlear implantation and MRI is a gold standard for CN detection. Some authors have reported the relationship between cochlear bony nerve canal (BCNC) stenosis and CN hypoplasia and aplasia. Objectives: The aim of this study was to stress out the importance of CT by evaluating the width of the bony cochlear nerve canal (BCNC) in children with congenital sensorineural hearing loss (SNHL) and “normal" findings on thin section temporal bone CT. Materials and methods: The width of the BCNC was retrospectively evaluated in two groups of patients. The study group included 11 children with congenital, bilateral SNHL who underwent cochlear implantation from July to December 2019. Eleven children aged 3-10 years, with no sensorineural hearing loss were taken as controls. Axial sections of their CT scans were used to measure the width of the BCNC. Results: From the obtained results, the width of the BCNC in children with bilateral, profound sensorineural hearing impairment range from 1.0 to 2.3 mm with mean value of 1.5 ± 0.3 mm and is significantly smaller than in the control group.
Keywords: bony cochlear nerve canal; children; congenital sensorineural hearing loss; CT